Isolation and characterisation of cDNAs encoding the large and small subnits of ADP-glucose pyrophosphorylase from cassava (Manihot esculenta Crantz) - Munyikwa, TRI; Kreuze, Jan F.; Fregene, Martin A.; Suurs, L; Jacobsen, E; Visser, Richard G.F. (Springer, 2001)
Screening of a tuber specific cassava cDNA library resulted in the isolation of full length cDNA clones with homology to the genes encoding the small and large subunits of ADP glucose pyrophosphoryalse. Sequence analysis revealed that AGPase B the clone with homology to the small subunit shared 54% homology at amino acid level with the AGPase S clone that is more closely related to the large subunit. Segregation analysis of a cross between the cassava cultivars TMS 30572 and CM 2177-2 revealed that AGPase S is a single copy gene that is localised on the female derived linkage group E of the cassava genetic map. AGPase B is a low copy gene of which one member is localised on the female derived linkage group P. The two genes are expressed in all cassava tissues but AGPase B exhibits a higher steady state mRNA level than AGPase S and is highly expressed in leaf and tuber tissue. The AGPase enzyme activity was much higher in young cassava leaves as compared to older leaves and tubers. Cassava AGPase was activated by 3-PGA and inhibited by up to 90% in the presence of inorganic phosphate (Pi). The tuber enzyme was relatively unaffected by 3PGA but was highly inhibited by Pi. Transformation of potato (Solanum tuberosum) plants with an antisense AGPase B construct resulted in 10 out of 134 antisense AGPase B plants having on average 3.5 times more tubers than the control non transgenic plants. Analysis of these transgenic plants revealed they had greatly reduced levels of AGPase B mRNA, 1.5 to 3 times less starch, and five times higher levels of soluble sugars, sucrose, glucose and fructose, to those found in control plants.